A metrological inspection method using micro-CT for the analysis of drilled holes in CFRP and titanium stacks - Kourra, Nadia; Warnett, Jason; Attridge, Alex; Dahnel, Aishah Najiah; Ascroft, Helen; Barnes, Stuart; Williams, Mark; , (Springer, 2017)
This paper demonstrates a novel method that combines X-ray computed tomography (CT) and image processing for investigating two materials with significantly different densities. CT is increasingly used in industrial applications of inspecting materials and defects. The limitations of the system and data reconstruction are continuously researched so as to improve the quality of the results. One of the most common issues in CT is beam hardening, frequently experienced in multi-material scanning. The materials examined to demonstrate the method are carbon fibre reinforced polymers (CFRP) and titanium alloy Ti6Al4V, often used in combination in industry to optimise the weight to strength ratio. The assembly of the materials is usually achieved by bolting and riveting, which requires drilling through the two materials together. The machining of these materials is difficult due to their higher specific properties and as a result tool wear is always an issue. CFRPs properties depend on the nature, orientation and bond of the fibres and as a result drilling affects their service life. The results of the method ensure the quality of the drilled holes by measuring the variation of the maximum diameter, circularity, positioning of the hole and an examining the entrance delamination and exit burrs by image processing.